2022
DOI: 10.1302/2046-3758.1112.bjr-2022-0152.r1
|View full text |Cite
|
Sign up to set email alerts
|

Volume and location of bone regeneration after autologous expanded mesenchymal stromal cells in hip osteonecrosis

Abstract: Aims Successful cell therapy in hip osteonecrosis (ON) may help to avoid ON progression or total hip arthroplasty (THA), but the achieved bone regeneration is unclear. The aim of this study was to evaluate amount and location of bone regeneration obtained after surgical injection of expanded autologous mesenchymal stromal cells from the bone marrow (BM-hMSCs). Methods A total of 20 patients with small and medium-size symptomatic stage II femoral head ON treated with 140 million BM-hMSCs through percutaneous fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A recent study using autologous BMSCs reported that the mean threshold residual lesion volume for progression of collapse was 10% (standard deviation 6%) at three months after implantation. 32…”
Section: Delivery Of the Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study using autologous BMSCs reported that the mean threshold residual lesion volume for progression of collapse was 10% (standard deviation 6%) at three months after implantation. 32…”
Section: Delivery Of the Cellsmentioning
confidence: 99%
“…A recent study using autologous BMSCs reported that the mean threshold residual lesion volume for progression of collapse was 10% (standard deviation 6%) at three months after implantation. 32 Safety is one of the critical concerns in the application of cell therapy. Key features of stem cells such as selfreplication, long lifespan, and multidifferentiation are also shared by cancer cells.…”
Section: Delivery Of the Cellsmentioning
confidence: 99%
“…[12][13][14][15][16][17] have been applied to evaluate the efficiency of those biomaterials on osteogenesis, and MSC treatments even achieved profound success in clinical trials for bone regeneration. 18,19 Due to the accumulated studies, MSCs can now be cultured without sophisticated instruments and unique medium, and commercial MSCs are also available. 20 Thus, MSCs can be cultured and tested in most laboratories worldwide.…”
mentioning
confidence: 99%